2016
DOI: 10.1080/ac.71.2.3141849
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic significance of serum galectin-3 levels in heart failure with preserved ejection fraction

Abstract: Our results support that, in addition to NT-proBNP, galectin-3 is also a valuable biomarker for the diagnosis of patients with HFpEF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 0 publications
1
20
0
1
Order By: Relevance
“…28 Consistent with our study, Polat and coworkers also demonstrated that NT-proBNP levels were significantly elevated in patients with HFpEF when compared with controls (p < 0.0001). 25 In our study, serum Galectin-3 has shown a positive correlation with NT-proBNP (r = 0.21, p = 0.048). Consistent with our study, Chen et al have reported a positive correlation of Galectin-3 with NT-proBNP levels (r = 0.399, p < 0.01).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…28 Consistent with our study, Polat and coworkers also demonstrated that NT-proBNP levels were significantly elevated in patients with HFpEF when compared with controls (p < 0.0001). 25 In our study, serum Galectin-3 has shown a positive correlation with NT-proBNP (r = 0.21, p = 0.048). Consistent with our study, Chen et al have reported a positive correlation of Galectin-3 with NT-proBNP levels (r = 0.399, p < 0.01).…”
Section: Discussionsupporting
confidence: 59%
“…24 Similar results were also observed by Polat et al, who reported that Galectin-3 levels were significantly increased in patients with HFpEF when compared with controls (p < 0.0001). 25 Zile and colleagues also demonstrated in one small series that Galectin-3 levels were significantly elevated in a cohort of patients with HFpEF. 26 Experimental studies suggest that Galectin3 is important for the development and progression of HFpEF.…”
Section: Discussionmentioning
confidence: 92%
“…In the CORONA study, 1492 patients with heart failure caused by ischemic myocardiosis were randomly divided into a Rosuvastatin treatment group and a control group: the mortality of the statin group was lower than that of the control group and Gal-3 decreased significantly in the statin group [80]. Polat et al found that Gal-3 played an important role in prevention, classification, and personal therapy of heart failure [81]. Aforementioned studies revealed the clinical significance of Gal-3 in atherosclerosis-associated heart failure, but the mechanism of Gal-3 leading to heart failure needs to be further detected.…”
Section: Gal-3 and Heart Failurementioning
confidence: 99%
“…It was demonstrated in animal models that galectin-3 contributes to the development and progression of heart failure through cardiac fibrosis and adverse structural remodeling [12]. Recent studies indicate that galectin-3 may reflect the presence of echocardiographically assessed heart failure with preserved ejection fraction (HFpEF) better than NT-proBNP due to a higher degree of cardiac fibrosis as a consequence of a chronically increased afterload during arterial hypertension [1315]. Also galectin-3 was shown to correlate with LVEF in cMRI in patients after myocardial infarction [16] and to serve as a strong prognostic biomarker in chronic stages of heart failure [1719].…”
Section: Introductionmentioning
confidence: 99%